10-Year oncological outcome report after second conservative treatment for ipsilateral breast tumor event - Jean-Michel Hannoun-Levi; Jocelyn Gal; Renaud Schiappa; Marie-Eve Chand (Clinical and Translational Radiation Oncology, 2023)
Purpose: To analyze long-term oncological outcome after 2nd conservative treatment (2ndCT) for patients with ipsilateral 2nd ipsilateral breast tumor event (2ndIBTE). Materials/methods: In this retrospective observational study (N°F20210402152843), patients with 2ndIBTE underwent 2ndCT (lumpectomy + tumor bed re-irradiation). 3rdIBTE (3rdIBTE-FS), regional relapse- (RRFS) and metastatic disease- (MD-FS) free survivals as well as disease-free (DFS), specific (SS) and overall (OS) survival were analyzed. Late toxicity was reported. Results: Between 09/2000 and 04/2022, 244 patients presented a 2ndIBTE and underwent a 2ndCT. Among them, 113 pts with a minimum follow-up of 60 months were analyzed. Median time interval between 1st and 2ndIBTE was 13.5 years [2–35]. Median 2ndIBTE age was 66.2 years [31–85]. 2ndIBTE were adenocarcinomas (77 %). Tumor size was < 20 mm (86.7 %). 2ndIBTE were grade 1/2 (75 %), with positive hormonal receptor (85 %) and clear surgical margins (no ink on tumor, 90.3 %). In the APBI classification, 21 pts were high-risk (18.6 %), while 77 % were Luminal A/BHer2-. With a MFU of 121.5 months [CI95% 111.7–129.6], 10-year 3rdIBTE-FS was 89 % [83–96]. Then-year RRFS, MDFS, DFS, SS and OS were 94 % [89–100], 89 % [83–96], 78 % [70–87], 95 % [91–100] and 94 % [90 –99] respectively. In multivariate analysis, APBI classification (high-risk; HR2.66 [1.01–7.1], p = 0.049) and tumor size (≥20 mm; HR2.64 [1.02–6.8], p = 0.045) were considered independent prognostic factors for DFS.Ninety-seven late complications were observed (fibrosis 64 %) with 6.2 % G ≥ 3 late toxicity. Cosmetic outcome was excellent/good in 91.2 %. Conclusions: With long follow-up, 2ndIBTE managed with 2ndCT allows second breast preservation without oncological outcome compromise and acceptable G ≥ 3 toxicity.